2006
DOI: 10.1177/154405910608500312
|View full text |Cite
|
Sign up to set email alerts
|

Novel MSX1 Frameshift Causes Autosomal-dominant Oligodontia

Abstract: Can kindreds with tooth agenesis caused by MSX1 or PAX9 mutations be distinguished by their phenotypes? We have identified an MSX1 frameshift mutation (g.62dupG, p.G22RfsX168) that causes non-syndromic autosomal-dominant oligodontia, featuring the absence of multiple permanent teeth, including all second bicuspids and mandibular central incisors. The dominant phenotype is apparently due to haploinsufficiency. We analyzed patterns of partial tooth agenesis in seven kindreds with defined MSX1 mutations and ten k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 32 publications
4
83
0
12
Order By: Relevance
“…Previous studies have mainly focused on tooth agenesis, associating the MSX1 variants to the type and number of missing teeth, and it is generally concluded that the most frequently missing teeth in case of MSX1 variants are the second premolars. [13][14][15] In a previous study we identified a novel MSX1 mutation causing tooth agenesis with cleft lip, further confirming that different MSX1 mutations may cause different phenotypes. 16 This review reveals a strong correlation between observed phenotypes and the location in the MSX1 protein structure of the disease causing mutations.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have mainly focused on tooth agenesis, associating the MSX1 variants to the type and number of missing teeth, and it is generally concluded that the most frequently missing teeth in case of MSX1 variants are the second premolars. [13][14][15] In a previous study we identified a novel MSX1 mutation causing tooth agenesis with cleft lip, further confirming that different MSX1 mutations may cause different phenotypes. 16 This review reveals a strong correlation between observed phenotypes and the location in the MSX1 protein structure of the disease causing mutations.…”
Section: Introductionsupporting
confidence: 57%
“…25 MSX1 and non-syndromic tooth agenesis Non-syndromic tooth agenesis (ns TA) is another common developmental anomaly that can be caused by MSX1 variants. 14 To date, nearly 20 MSX1 mutations have been related to ns TA 8,13,[26][27][28][29][30][31][32][33][34][35][36][37] (Table 2). Functional analyses of the mutant proteins suggest that haploinsufficiency of MSX1 underlies this phenotype.…”
Section: Disease Phenotypes Caused By Msx1 Mutationsmentioning
confidence: 99%
“…The typical feature of MSX1-associated tooth agenesis is frequent absence of UP1, UP2 and/or LP2, whereas the typical feature of PAX9-associated tooth agenesis is frequent absence of UM2 and/or LM2. 48 Some individuals with a PAX9 mutation lack UPs, LPs and/or LI1. 9 PAX9 is a dosagesensitive gene in humans, and its function appears to be most relevant in the posterior teeth, especially in those derived from the proliferation of the dental lamina from which permanent molars originate.…”
Section: Discussionmentioning
confidence: 99%
“…This gene also establishes the place and time of organ initiation or morphogenesis. Furthermore, it has been suggested that PAX9 acts in marking mesenchymal-specific sites where future teeth will form (Kim et al 2006).…”
Section: Roles Of the Msx1 And Pax9 Genesmentioning
confidence: 99%